A new species of the genus Truncocolumella (Basidiomycota, Boletales) found in the Hengduan Mountains of China - Lin Li; Shanping Wan; Yun Wang; Naritsada Thongklang; Zonglong Luo; Shuhong Li (Biodiversity Data Journal)
During surveys of hypogeous fungi in the Hengduan Mountains, south-western China, three specimens of the genus Truncocolumella were discovered in Sichuan Province.Morphological and molecular analyses revealed that the collections represent a new species, Truncocolumella pseudocolumella. This article describes the new species and discusses its relationship with the other two members of the genus.